THE MAIN OBSTACLES TO THE USE OF TECHNOLOGY IN PHYSICAL EDUCATION LESSONS FOR SECONDARY SCHOOL STUDENTS - Ameen Atta Hassan (Universitas Negeri Jakarta, 2025)
Background. The incorporation of technology in education has emerged as a crucial factor in improving teaching and learning methodologies. Nonetheless, the application of technology in physical education (PE) is still restricted in comparison to other fields. This study examines the primary challenges that impede the effective integration of technology in physical education classes for secondary school students. Objectives. The research seeks to pinpoint the primary challenges encountered by physical education teachers in the integration of technological tools and to examine the factors that affect their utilization in both classroom and field-based instruction. Method. The research utilized a descriptive survey methodology. The target population comprised 122 physical education instructors from intermediate and secondary institutions associated with the General Directorate of Education in Wasit. A purposive sampling technique was used to choose 80 teachers (65.57%) from a group of 80. A validated and reliable questionnaire with 38 items spread across several dimensions was used to collect data. The instrument was administered electronically through Google Forms, and the data were analyzed utilizing descriptive and inferential statistical methods. Results. The findings indicated that the principal barriers to technology integration encompassed inadequate administrative and technical support, insufficient digital infrastructure, limited teacher proficiency in utilizing technological devices and software, a deficiency of digital teaching resources, and ambiguous institutional policies. These barriers show that technology adoption is limited by a combination of technological, human, and organizational factors. Conclusion. The study finds that for technology to be successfully integrated into physical education, teachers need to be trained in a systematic way, the infrastructure needs to be improved, and administrative support needs to be consistent. Creating a strategic vision for digital transformation in physical education can give teachers the tools they need to use technology effectively and help students learn more and be more interested in what they're learning.